Brand Trust as a Mediator Service Quality and Product Quality on Purchasing Decisions at Sejuta Jiwa Coffee Surabaya - Amanda Putri Desynta; Taufik Setyadi; Fatchur Rozci (Universitas Negeri Padang, 2026)
The purpose of this study is to explore the impact of service and product quality on purchasing decisions, considering brand trust as a mediator among Kopi Sejuta Jiwa consumers in Surabaya. The approach used is quantitative with a population consisting of Kopi Sejuta Jiwa buyers in Surabaya. The research sample consisted a total of 100 respondents were chosen through accidental sampling. Data collection was conducted via questionnaires and subsequently analyzed using Structural Equation Modeling (SEM), including testing measurement models and structural models, and a bootstrapping process using SmartPLS 4.0 software. Based on the results of data analysis, this study found that good service makes consumers more likely to buy a product. Product quality also influences purchasing decisions. In addition, satisfactory service increases consumer trust in the brand. Brand trust significantly influences purchasing decisions and functions as a mediator in the relationship connecting service quality with purchasing behavior, while product quality does not significantly influence brand trust, and brand trust does not play a mediating role between product quality and purchasing decisions. The results of the study also indicate that product quality and service quality have a significant impact on brand trust and purchase decisions. The coefficient of determination (R²) indicates that the model explains 43% of the variation in brand trust and 69% of the variation in purchase decisions. These findings indicate that factors beyond brand trust influence purchasing decisions at Kopi Sejuta Jiwa Surabaya